Social justice pedagogy: International perspectives on Collaborative Online International Learning (COIL) through a World Café engagement - Karen S. Collett; Alina Slapac (Journal of Virtual Exchange)
The promotion of social justice pedagogy in Collaborative Online International Learning (COIL) courses and virtual exchange (VE) programs has gained traction in the last decade, as opportunities for faculty and students to participate as equal partners in the internationalization of the curriculum have grown. This practice report highlights the processes and outcomes of critical engagement through an interactive World Café workshop at the 2023 IVEC conference in São Paulo, Brazil. The participants were a group of 45 international faculty and COIL coordinators from various higher education institutions. Nancy Fraser’s (2008; 2009) normative framework related to social justice was used to facilitate a critical discussion related to the economic, cultural, and political dimensions of their COIL courses in supporting participatory parity. Key trends, questions, and recommendations for enhancing social justice pedagogy were identified. These findings may provide a springboard to engage colleagues in further dialogue that could promote awareness around social justice pedagogy and participatory parity through COIL.